Exploring the metafunctions to improve EFL learners’ writing ability in the perspective of systemic functional linguistics - Herman, Herman; Rafiek, Muhammad; Agustina, Titik; Saddhono, Kundharu; Malabar, Sayama; Saputra, Nanda; Purba, Ridwin (Research Journal in Advanced Humanities, 2023)
Writing in academic English is challenging and complex to learn, the root reasons for the issue, may include differences in the cultural backgrounds of the students, a deficiency in critical thinking skills, and a deficiency in linguistic proficiency. This study set out to investigate how metafunctions may be used to enhance students' writing skills. A research approach incorporating a qualitative case study will be employed to assess ninth-grade students' text composition. The data were gathered through collecting student writing over the school year 2021/2022. The students’ writings were the texts that were learnt in grade nine based on the curriculum. This study used Systemic Functional Linguistic theory and English texts to provide the framework for the text analysis. The texts were analyzed using the metafunction analysis in Hallidayan SFL to uncover the students’ ability to write English text. The teacher applied the Genre-based Approach when instructing his or her students on how to write. The results presented that metafunctions analysis was very important because there were ideational, interpersonal, and textual metafunctions. The ideational metafunction revealed the use of some processes in the students’ writing (material, mental, relational, and verbal), interpersonal revealed the importance of mood and residue elements in students’ writing and textual metafunction showed the importance of thematic progression pattern. This study indicated that to alleviate students’ challenges and strengthen their academic writing and critical thinking capacity, teachers should have a better understanding of the theory of Systemic Functional Linguistics.